Social and Support Services Offered by Cleft and Craniofacial Teams: A National Survey and Institutional Experience. Issue 2 (March 2016) - Ascha, Mona; McDaniel, Jarred; Link, Irene; Rowe, David; Soltanian, Hooman; Sattar, Abdus; Becker, Devra; Lakin, Gregory E.
Abstract : Background: A multidisciplinary approach to patients with craniofacial abnormalities is the standard of care by the American Cleft Palate-Craniofacial Association (ACPA). The standards of team care, however, do not require provision of social support services beyond access to a social worker. The purpose of this investigation is to study social support services provided by ACPA teams, funding sources for services, and family interest in services. Methods: A survey was submitted to ACPA cleft and craniofacial team leaders (N = 161), which evaluated the provision of potentially beneficial social support services, and their funding sources. A second survey administered to patient families at our institution gauged their level of interest in these services. Statistical analysis evaluated the level of interest among services. Results: Seventy-five of 161 (47%) teams and 39 of 54 (72%) families responded to the surveys. Services provided included scholarships (4%), summer camp (25%), social media (32%), patient support groups (36%), parties (42%), parent support groups (46%), other opportunities (56%), and social workers (90%). The majority of funding for social workers was by the institution (61%) whereas funding for ancillary services varied (institution, team, fundraisers, grants, and other sources). Families indicated an average interest of 2.4 ± 1.41 for support groups, 2.5 ± 1.63 for summer camps, 2.92 ± 1.66 for parties, 3.16 ± 1.65 for social media, and 3.95 ± 1.60 for scholarships ( P value <0.05). Conclusions: The ACPA standards of team care do not require teams to provide social support services beyond access to a social worker. Among our survey respondents, the authors found that in addition to a social worker, teams offered social support services, which were not required. The social worker position is usually institutionally funded, whereas funding sources for additional services varied. Respondents at our center desired additional social support services. The authors recommend a hybrid model of hospital and nonhospital funding to provide social and support services to patients with craniofacial deformities.